Irrigation frequency effects on Prizm zoysiagrass establishment from sprigs - Tyler Q. Carr; John C. Sorochan; James, T. Brosnan; Brandon J. Horvath; Kellie. J. Walters (Agrosystems, Geosciences & Environment)
Abstract Zoysiagrass (Zoysia spp. Willd.) is a popular choice for commercial and residential lawns, as well as golf course fairways and tees because it requires less light, fertilizer, and mowing compared to bermudagrass (Cynodon spp.). However, zoysiagrass' slow growth rate compared to other putting green options presents a challenge for both rapid establishment from sprigs and its wider adoption as a putting green surface. It is currently unknown if very frequent irrigation, commonly used in horticultural propagation, can be applied to turfgrass and accelerate establishment from sprigs. Irrigation was applied to Prizm zoysiagrass sprigs across either four or 192 irrigation events from 06:00 a.m. to 10:00 p.m. Prizm zoysiagrass establishment was unaffected by irrigation frequency and averaged 40% turfgrass coverage after 21.6 and 27.3 days in run A and run B, respectively. These results imply that very frequent irrigation did not accelerate establishment. Additional research elucidating zoysiagrass sprig physiology during propagation and development is necessary to better define management practices that hasten establishment.